Peningkatan Minat Dan Hasil Belajar MatematikaMelalui Strategi Talking Stick Pada Siswa Kelas V SDN 02 Puntukrejo Kecamatan Ngargoyoso Tahun Ajaran 2015/2016 - Hartono, Daisy Putriasih, Dra. Risminawati, M.Pd (2016)
The purpose of this study are: (1) To increase interest in learning mathematics through a strategy of talking stick in the fifth grade students of SDN 02 Puntukrejo Ngargoyoso District of School Year 2015/2016. (2) To improve mathematics learning outcomes through strategies talking stick in the fifth grade V SDN 02 Puntukrejo Ngargoyoso District of School Year 2015/2016. This type of research is a class action. This classroom action research consisted of two cycles, each cycle consists of four stages: planning, execution, observation, reflection. The subjects in this study is the teachers and students of class V SDN 02 Puntukrejo District of Ngargoyoso totaling 26 students. Data collection techniques used in this study, observation, interviews, tests, and documentation. Data analysis technique used is qualitative analysis by Miles and Huberman interactive model that consists of three activities, namely the flow of data reduction, data presentation, drawing conclusions. The results of the study of this class action, namely: (1) an increase in students' interest in learning mathematics, at the beginning before the measure student interest amounted to 39.18%, in the first cycle student interest increased to 57.44%, and the second cycle interest in learning students increased to 83.42%. (2) an increase in students' mathematics learning outcomes, at the beginning before the measure student learning outcomes at 43.46%, in the first cycle learning outcomes of students increased to 58.46%, in the second cycle learning outcomes of students increased to 81.15%. Based on the results of action research above it can be concluded that by using talking stick strategy can increase interest andlearning outcomes math grade students of SDN 02 Puntukrejo Ngargoyoso District of School Year 2015/2016. Keywords: learning outcomes, mathematics, interest in learning, strategies talking stick